Analisis Kesulitan Belajar Siswa pada Materi Geometri dikelas VI SD IT Inayah Ujung Batu - Khoirul Mardongan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study meant to analyse excahnge the learning hardship of level VI students of SD Islam Terpadu Inayah Ujung Batu in answering geometry questions, the results of which are to determine will seen view of tthe difficulties and the aspect in causing the lurch of mathematic a geometry. This research design is medical study where the centered a focused on only one selected phenomenon and wants to be understood in depth by ignoring other phenomena. The approach used is a qualitative approach. Then the method used is an descriptive. The results of this study aim to determine where the difficulties of the students are. the results of research can be used as material for developing problems, especially in geometry material. The results showed that the learning difficulties of grade VI students in understanding geometry were: 1 The students were less able to understand geometry because part of the learning was done online. 2 difficulties in understanding the concept. 3 students have difficulty in using principles. Student Difficulties in solving verbal problems.